Kerapuhan Keutuhan Keluarga Perempuan Bersama Suami Biseksual - Salma Salma; Fadly Yunandri; Yecki Bus (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
This study was based on the existence of wive's divorce after knowing their husband have same-sex sexual orientation. Husband's behavior as homosexual had triggered conflict in their marriage. This normative legal study was carried out by analysing of the decision of Padang Religious Court Number 0783/Pdt.G/2017/PA.Pdg and Number 0266/Pdt.G/2018/PA.Pdg as well as other secondary legal materials such as laws and regulations, Jurisprudence and other related books. The results showed that the husband's homosexual behavior was unknown to the wife since before marriage but they found it after a long time living the marriage life. Wives found their husbands having sexual relations or the husband himself confessed his actions. Based on the legislation, the wife as a disadvantaged person might file for divorce on the grounds that the husband behaves homosexually even though the regulation could only justify by mentioning a constant dispute. In addition, it was impossible for a marriage to be built and be able to achieve its goals when the husband was not only homosexual but also bisexual. Homosexuality itself in Islamic law was part of a heinous act which was severely punished by the culprit.